The Effect of Pricing and Product Quality on Consumer Buying Interest of Honda PCX Motorcycles at PT Primadelta Starlestari Rangkasbitung - Maesaroh, Maesaroh; M. Annas Al Ansyori (Edupedia Publisher, 2025)
This research determines the factors influencing consumer buying interest through pricing and product quality at the company PT Primadelta Starlestari Rangkasbitung. The objectives of this research are (1) to determine the effect of price determination on consumer buying interest, (2) to find out the effect of product quality on consumer buying interest, (3) to find out price setting and product quality on consumer buying interest at PT Primadelta Starlestari Rangkasbitung. The method used in this research is the Quantitative Descriptive research method. The sampling technique is simple random sampling, which provides equal opportunities for each element (member). The sample from this research consists of 78 respondents. This research was tested using the classical assumption test, then analyzed using correlation tests and multiple linear regression tests using the SPSS VERSION 20 program. The research results showed an influence of pricing and product quality on consumers' buying interest in Honda PCX motorbikes at PT Primadelta Starlestari Rangkasbitung.